The Influence of Digital Competence and Knowledge Sharing on Employee Performance with Work Motivation as an Intervening Variable - Sukma Dhaniswara, Angga; Susita, Dewi; Wahono, Puji (International Journal of Social Science, Education, Communication and Economics, 2024)
Taxes play an essential role in realizing the vision of "Indonesia Emas 2045". Low tax ratios and voluntary taxpayer compliance influence the achievement of tax revenues. The causal factor is that the quality of education provided is not optimal because the number of tax educators is still limited. The DGT report stated that digital competence, knowledge sharing, and tax instructors' work motivation needed to be improved. This research aims to determine the effect of digital competence and knowledge sharing on employee performance with work motivation as an intervening variable for tax educators at the Directorate General of Taxes. The research methodology uses quantitative survey methods. The population is 2,340 employees, with a total of 342 respondents. The hypothesis was tested using PLS-SEM analysis using Smart-PLS version 4, SPSS Version 27, and the Embedded Two-Stage Approach method. The research results show that digital competence and work motivation have a significant positive influence on employee performance. Knowledge sharing does not have a significant effect on employee performance. Digital Competence and Knowledge Sharing positively and significantly affect work motivation. Work motivation significantly mediates the indirect effect of digital competence and knowledge sharing on employee performance.